Circadian disturbances, anxiety and motor disturbances differentiate delirium superimposed on dementia from dementia-only - Schnorr, Thiemo; Fleiner, Tim; Trumpf, Rieke; Prüter-Schwarte, Christian; Fanselow, Janina; Zijlstra, Wiebren; Haussermann, Peter (Frontiers in Psychiatry, 2024)
Background: To ensure adequate treatment, individuals with delirium superimposed on dementia (DSD) need to be differentiated reliably from those with dementia only (DO). Therefore, we aimed to examine the clinical indicators of DSD by assessing motor subtypes, cognitive performance and neuropsychiatric symptoms in DSD and DO patients. Methods: Cross-sectional design with the Delirium-Motor-Subtyping Scale (DMSS), Mini-Mental-State-Examination (MMSE), Clock-Drawing-Test (CDT), DemTect, and Neuropsychiatric Inventory assessed after admission to an acute hospital. Results: 94 patients were included, 43 with DSD (78±7 years, MMSE = 11±9) and 51 with DO (79±7 years, MMSE = 9±8). DMSS "no subtype" was more common in the DO group (26% vs. 10%, p =.04). The DSD group showed lower CDT scores (DSD: M = 4±3 vs. DO: M = 6±1; p<.001) and higher anxiety (DSD: MED = 3±8 vs. DO: MED = 3±4; p=.01) and sleep/night-time behavior disturbances (DSD: MED = 0±6 vs. DO: MED = 0±0; p=.02). Conclusions: Sleep/night-time behavior disturbances appear to be a clinical indicator of DSD. Motor subtypes can identify cases at increased risk of developing delirium or unrecognized delirium. Trial registration: Trial registration number: DRKS00025439 (German Clinical Trials Register).The Ethics Committee of the North Rhine Medical Association approved all procedures (reference number 2018912).